2012
DOI: 10.1111/j.1365-2702.2012.04239.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the levels of nurses’ competence and the length of their clinical experience: a tentative model for nursing competence development

Abstract: The level of nursing competence directly affects the quality of care provided to patients. The findings of the study enable healthcare organisations to take proactive approaches to enhance nurses' competence by identifying when and how to assist nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 37 publications
5
54
0
3
Order By: Relevance
“…In Model 1, the effects of the demographic variables were controlled for, because the previous studies indicated that nurses' self-reported competence differed depending on the years of clinical experience (Takase, 2013), educational background (Takase et al, 2014), and clinical specialty (Meretoja et al, 2004b). In particular, a study by Takase (2013) suggested that nurses' self-reported competence increased rapidly for the first 10 years (most prominently, in the first 5 years). Therefore, the years of clinical experience were entered in the regression model, even though the participants were classified into two experience groups.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In Model 1, the effects of the demographic variables were controlled for, because the previous studies indicated that nurses' self-reported competence differed depending on the years of clinical experience (Takase, 2013), educational background (Takase et al, 2014), and clinical specialty (Meretoja et al, 2004b). In particular, a study by Takase (2013) suggested that nurses' self-reported competence increased rapidly for the first 10 years (most prominently, in the first 5 years). Therefore, the years of clinical experience were entered in the regression model, even though the participants were classified into two experience groups.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, having the same amount of experience does not mean that nurses possess the same level of competence. This is because the development of nursing competence does not depend only on the amount of experience, but may also be influenced by what and how much they learn from that experience (i.e., the quality of experience) (Takase, 2013). This highlights the importance of evaluating the extent of learning that nurses gain from everyday practice, and of relating this to the development of nursing competence.…”
Section: Workplace Learning and Competence Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies investigating ‘overall holistic nursing competence’ identified that the overall holistic nursing competencies increased among nurses with an increase in their clinical expertise, in the rewards provided by the organization, and in self‐reflection and insight; the competencies were observed to decrease with the increase in the desires to leave the organization (Eng & Pai ; Takase et al. ; Takase ; Takase et al. , ).…”
Section: Introductionmentioning
confidence: 99%
“…A plateau is reached after about ten years of nursing experience. 17 On average, both supplemental and permanent nurses had more than ten years of nursing experience, and the three-year average difference would have little effect on their competency levels.…”
Section: Growth In Supplemental Nurses 1984-2008mentioning
confidence: 99%